Implementasi Progressive Web Apps Pada Platform Freelance Digital Dengan Metode Rapid Application Development - Reyhan Adi Saputra; Irwan Alnarus Kautsar; Novia Ariyanti; Cindy aurusta (LPPM UBHINUS MALANG, 2024)
In recent years, the number of freelancers in Indonesia has increased significantly. Many people choose to become freelancers because they can work more flexible hours, have greater earning potential, and have more control over the work they do. Freelancers can also provide work to partners on digital freelance platforms when orders pile up and cannot be handled alone. The digital freelance platform provides a space where partners and freelancers can connect flexibly via the website, however visiting the website's Uniform Resource Locator (URL) is done repeatedly when you want to visit the platform. Progressive Web Apps (PWA) is a solution to this problem. This research aims to implement PWA on a digital freelance platform. The method used is the Rapid Application Development (RAD) method with stages of Requirements Planning, Design Workshop, and implementation. The research results show that PWA has been successfully implemented on digital freelance platforms. This is proven by the results of tool testing from web browsers, manual installation testing on the main screen, responsive testing, and service worker testing with black box. User response test results show that PWA is well received by users. This is proven by the results of the questionnaire which shows that the average percentage of user satisfaction is 93.5% in the